Airport dominance and airline pricing power: An investigation of hub premiums in the Chinese domestic market. (September 2017) - Chen, Ruowei; Lei, Zheng
Highlights: This research analyses the effects of airport dominance on airline pricing power with the empirical study from China. The market is segmented by premium and economy classes. Fixed-effects panel data models are employed to control for the carrier-route specific characteristics. Results indicate that airport dominance is the most important source of pricing power in the Chinese domestic market. Abstract: This research analyses the effects of airport dominance on airline pricing power with the empirical study based on the Chinese domestic market using fixed-effect panel data models. Results from the regression analysis indicate that airport dominance is the most important source of pricing power in the gradually deregulated Chinese domestic market. Hub carriers are able to charge higher prices to premium class passengers and non-hub carriers benefit from the "umbrella effects" of hub premiums. However, hub carriers are not able to translate their airport dominance to pricing power in the economy class market, whereas non-hub carriers even have to reduce the prices as their market shares at major airports increase. This study contributes to the literature by explicitly segmenting the market into economy and premium classes. The results have important policy implications in terms of further deregulation of Chinese domestic market.